Dinâmica da economia e da agropecuária no Matopiba - Antonio Marcio Buainain; Junior Ruiz Garcia; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The study seeks to analyze the importance of agricultural production in Matopiba, comprising areas in the states of Maranh\~ao, Tocantins, Piauí and Bahia, for economic development. The agricultural economic dynamics of Matopiba region becomes central in guiding the decisions of private actors in promoting regional development and the most appropriate formulation of public policies to local realities. The scientific problem here is to question whether the investments mobilized are in fact sustained, and in what extent agribusiness has the strength to lead developing poor states and with a high population density in rural areas. The hypothesis of this study is understood that agricultural policy can be an important tool for development, reducing inequalities and promoting sustainable management of natural resources in this region.
Keywords: Q1; Q17; Q28; 330; agricultural policy; development; agricultural frontier